2013
DOI: 10.1063/1.4795501
|View full text |Cite
|
Sign up to set email alerts
|

Local solid phase growth of few-layer graphene on silicon carbide from nickel silicide supersaturated with carbon

Abstract: Patterned few-layer graphene (FLG) films were grown by local solid phase epitaxy from nickel silicide supersaturated with carbon, following a fabrication scheme which allows the formation of self-aligned ohmic contacts on FLG and is compatible with conventional SiC device processing methods. The process was realised by the deposition and patterning of thin Ni films on semiinsulating 6H-SiC wafers followed by annealing and the selective removal of the resulting nickel silicide by wet chemistry. Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…This D and D'-bands comes from double-resonant processes and they are related to the presence of defects and structural disorder in graphene 31,32 . Therefore, the relative integrated intensity (area) ratio of the D and G bands, A(D)/A(G), in some works presented as I D /I G , is used to evaluate the defect concentration of the graphene films 25 . From the A(D)/A(G) ratio, it is possible to determine the cristallite size, L a , by using Eq.1,…”
Section: Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This D and D'-bands comes from double-resonant processes and they are related to the presence of defects and structural disorder in graphene 31,32 . Therefore, the relative integrated intensity (area) ratio of the D and G bands, A(D)/A(G), in some works presented as I D /I G , is used to evaluate the defect concentration of the graphene films 25 . From the A(D)/A(G) ratio, it is possible to determine the cristallite size, L a , by using Eq.1,…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Therefore, Si atoms will be sublimated and the graphitization will be able to occur, where the C atoms on the top of surface are rearranged to synthesize the epitaxial graphene 4,[16][17][18][19] . In order to create alternative processes, some studies have shown that the addition of a layer of "catalyst material" (such as Ni or Co) promotes the reduction of the temperature required for SiC decomposition [23][24][25][26] . Nevertheless, despite SiC dissociation is promoted in this case, the Si sublimation does not occur; rather a chemical reaction to form a silicide phase between the catalyst material and Si happens.…”
Section: Introductionmentioning
confidence: 99%
“…[149] Yoneda et al [145] and Escobedo-Cousin et al [149] reported the significant meaning of the face polarity effect for the Ni-mediated process. It was revealed that the thickness of Cface graphene (1ML [145], 1.7ML [149]) is smaller than that of Si-face graphene (2ML [145], 3.3ML [149]). Such a difference can be explained by a faster reaction rate for Ni with the Si-C bilayer than with the C-Si bilayers [145].…”
Section: Alternative Approaches To Graphene Synthesis On Sicmentioning
confidence: 99%
“…To elucidate the nature of the Ni-mediated graphene growth mechanism on silicon carbide, Escobedo-Cousin et al [149] experimentally studied the effect of the different growth conditions (Ni layer thickness, annealing temperature, and cooling rate) on the graphene formation. Based on the results of the XPS and Raman characterization, these authors conclude that (i) slowing the cooling rate leads to the formation of graphene layers with higher quality, (ii) higher annealing temperature promotes graphene formation with larger domain size and (iii) there is no a direct correlation between graphene thickness and Ni film thickness since the former tends to reach saturation with increasing the latter.…”
Section: Alternative Approaches To Graphene Synthesis On Sicmentioning
confidence: 99%
See 1 more Smart Citation